Dystrophin levels and clinical severity in Becker muscular dystrophy patients. Issue 7 (29th November 2013) - van den Bergen, J C; Wokke, B H; Janson, A A; van Duinen, S G; Hulsker, M A; Ginjaar, H B; van Deutekom, J C; Aartsma-Rus, A; Kan, H E; Verschuuren, J J
Abstract : Objective: Becker muscular dystrophy (BMD) is characterised by broad clinical variability. Ongoing studies exploring dystrophin restoration in Duchenne muscular dystrophy ask for better understanding of the relation between dystrophin levels and disease severity. We studied this relation in BMD patients with varying mutations, including a large subset with an exon 45–47 deletion. Methods: Dystrophin was quantified by western blot analyses in a fresh muscle biopsy of the anterior tibial muscle. Disease severity was assessed using quantitative muscle strength measurements and functional disability scoring. MRI of the leg was performed in a subgroup to detect fatty infiltration. Results: 33 BMD patients participated. No linear relation was found between dystrophin levels (range 3%–78%) and muscle strength or age at different disease milestones, in both the whole group and the subgroup of exon 45–47 deleted patients. However, patients with less than 10% dystrophin all showed a severe disease course. No relation was found between disease severity and age when analysing the whole group. By contrast, in the exon 45–47 deleted subgroup, muscle strength and levels of fatty infiltration were significantly correlated with patients' age. Conclusions: Our study shows that dystrophin levels appear not to be a major determinant of disease severity in BMD, as long as it is above approximately 10%. A significant relation between age and disease course was only found in the exon 45–47 deletion subgroup. This suggests that at higher dystrophin levels, the disease course depends more on the mutation site than on the amount of the dystrophin protein produced.